2015
DOI: 10.1159/000438677
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Associated with Visual Outcome after Pars Plana Vitrectomy with Internal Limiting Membrane Peeling for Idiopathic Epiretinal Membrane

Abstract: Purpose: Pars plana vitrectomy with internal limiting membrane peeling for idiopathic epiretinal membrane has shown varying results. More data are needed on the factors associated with visual outcome. Methods: We extracted baseline clinical characteristics, optical coherence tomography (OCT) characteristics and 3-month postoperative best-corrected visual acuity (BCVA). Linear regression analysis was used to evaluate whether baseline and OCT characteristics are associated with BCVA at 3 months as well as BCVA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
1
14
0
4
Order By: Relevance
“…As already proposed by Govetto et al [ 15 ], we believed that this association could be due to the combination of two factors: on one side, the physical traction on retinal layers with obstruction between the afferent light and the foveal photoreceptors, displacement and deformation of the photoreceptors alterating neurotransmission; on the other side, the reactive proliferation driven by Müller cells. Moreover, the lower preoperative BCVA is a negative functional prognostic factor itself [ 37 ]. The residual chronic alteration of foveal microanatomy in combination with the reactive reaction of Müller cells formation of bridge of retinal tissue in in the foveal area has been supposed to play a role in the lower postoperative functional recovery of patient with CEIFLs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As already proposed by Govetto et al [ 15 ], we believed that this association could be due to the combination of two factors: on one side, the physical traction on retinal layers with obstruction between the afferent light and the foveal photoreceptors, displacement and deformation of the photoreceptors alterating neurotransmission; on the other side, the reactive proliferation driven by Müller cells. Moreover, the lower preoperative BCVA is a negative functional prognostic factor itself [ 37 ]. The residual chronic alteration of foveal microanatomy in combination with the reactive reaction of Müller cells formation of bridge of retinal tissue in in the foveal area has been supposed to play a role in the lower postoperative functional recovery of patient with CEIFLs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to certain scholars, the preservation of the foveal photoreceptor inner/outer segment and external limited membrane may be key factors in the prognosis of BCVA ( 32 ). Laban et al ( 33 ) reported that OCT characteristics are not associated with post-operative BCVA and according to them, pre-operative BCVA is the most influential factor.…”
Section: Discussionmentioning
confidence: 99%
“…Выбор наблюдательной тактики в отношении пациентки имеет ряд оснований [12,14,15]. Во-первых, по результатам хирургического лечения вторичной ЭРМ, ассоциированной с тромбозом ветви ЦВС, повышение остроты зрения отмечено лишь у 48,5% пациентов [14], в то время как при лечении первичной ЭРМ -в 70% случаев [8].…”
Section: рис 1 динамика морфологических изменений сетчатки левого гunclassified
“…Во-вторых, у большинства пациентов с ЭРМ и относительно высокой остротой зрения (0,5 и выше) в отсутствие лечения зрительные функции остаются стабильными в течение 2 лет наблюдения, а снижение зрения происходит менее чем в 10% случаев [12]. В-третьих, наибольшая прибавка остроты зрения отмечается у больных с наименьшей остротой зрения до операции по поводу ЭРМ [8,15]. Кроме того, хирургия ЭРМ несет в себе такие необратимые субклинические эффекты, как фототоксичность интравитреального освещения, нейротоксичность трипанового синего в отношении ганглиозных клеток сетчатки, гибель значительного пула мюллеровых клеток в результате механической травмы при пилинге внутренней пограничной мембраны [17].…”
Section: рис 1 динамика морфологических изменений сетчатки левого гunclassified